Illumina next-generation sequencing reveals the complete mitochondrial genome of Psenopsis anomala (Perciformes: Centrolophidae) with phylogenetic consideration. (2nd September 2016) - Chen, Huapu; Che, Zhiwei; Li, Jiantao; Dai, Mingli; Xiang, Ling; Deng, Siping; Zhu, Chunhua; Huang, Hai; Li, Guangli
Abstract: Using Illumina next-generation sequencing (NGS), the complete mitochondrial genome of the Psenopsis anomala was sequenced in the present study. The mitochondrial genome of P. anomala is 16, 528 bp long and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. The structure about gene order and composition of P. anomala mitochondrial genome is similar to those of most other vertebrates. The nucleotide compositions of the light strand in descending order is 29.18% of T, 27.97% of G, 27.06% of A, and 15.79% of C. With the exception of the NADH dehydrogenase subunit 6 ( ND6 ) and eight tRNA genes, other mitochondrial genes are encoded on the heavy strand. The phylogenetic analysis by maximum-likelihood (ML) method shown that the Psenopsis anomala was closer to Peprilus triacanthus in the phylogenetic relationship.